The First Report of an Intraperitoneal Free-Floating Mass (an Autoamputated Ovary) Causing an Acute Abdomen in a Child - Ibrahim Uygun; Bahattin Aydogdu; Mehmet Hanifi Okur; Selcuk Otcu (Case Reports in Surgery)
A free-floating intraperitoneal mass is extremely rare, and almost all originate from an ovary. Here, we present the first case with an intraperitoneal free-floating autoamputated ovary that caused an acute abdomen in a child and also review the literature. A 4-year-old girl was admitted with signs and symptoms of acute abdomen. At surgery, the patient had no right ovary and the right tube ended in a thin band that pressed on the terminal ileum causing partial small intestine obstruction and acute abdomen. A calcified mass was found floating in the abdomen and was removed. The pathological examination showed necrotic tissue debris with calcifications. An autoamputated ovary is thought to result from ovarian torsion and is usually detected incidentally. However, it can cause an acute abdomen.